Adding bricks-to-clicks: An exploration to determine whether Millennials think Takealot should add Brick-and-mortar to its business model - Liphosa, Vhutali (The IIE, 2020)
Over the past couple of years, there has been a lot of focus on online retailing predicting it as the future of retail. However, in South Africa, only 2% accounts for the online retail spend, thus contradicting this prediction. In light of this, a new trend has emerged in which online only brands are expanding onto other channels of retail business. This is necessitated by the fact that millennials enjoy visiting stores and South Africa is known to have a dominant mall culture. It is for these reasons why this study followed an Interpretivists paradigm, with a qualitative methodology, using a cross-sectional hermeneutic phenomenological exploratory design and explored the online shopping and brick and mortar phenomenon and determine whether South African millennials think South Africa’s leading online retailer, Takealot, should add brick-and-mortar to its business model. To address the research problem, purposive and convenient sampling were employed to sample the millennial target population. Data was collected through standardised open ended semi-structured and in-depth interviews through Zoom Meetings platform which allowed the researcher to understand and explore millennials subjective perspectives of the phenomenon. Data was analysed using thematic analysis enabling the exploration of themes embedded in interview transcripts. Findings indicated that although online is predicted as the future, South African millennial consumers prefer to purchase products instore as they can experience them. Millennials channel choice is influenced by personal characteristics as well as the product type data revealed that electronics, clothing and appliances are suited instore while books are suited and preferred online. Additionally, searching of products online and then purchasing products instore is prevalent consumer behaviour. This implies that an experiential store would benefit Takealot and that seamless online experience needs to be maintained and enhanced as online is still used. Overall, this study contributes to the minimal research available pertaining the phenomenon and multichannel retailing and also serves to inform a business problem for Takealot and other online-only retailers.
Keywords: Online retail; Online brand; South Africa; Online shopping; Consumer behaviour